Faktor-Faktor yang Mempengaruhi Perdagangan Indonesia di Kawasan Amerika Latin - Sulthon Sjahril Sabaruddin (Universitas Muhammadiyah Prof. DR HAMKA., 2017)
This study tries to identify what factors influence the trade relations of Indonesia in Latin America with the approach of gravity model. The results of multiple regression analysis indicate that there are 4 (four) variables that affect the trade performance are: GDP Latin American countries, ex colonial countries of the Netherlands (ie Suriname), the existence of the Embassy and Latin AmericanEmbassy in Indonesia, as well as the number of MoU have positive effect on bilateral trade performance.From the results of the analysis can be concluded the initial expectation that the geographical distance into one of the obstacles in improving the trade relations of the Latin-American Republic to be less precise. In contrast, historical and emotional closeness factors appear to positively affect the trade relations between Indonesia and Latin America. This can be seen from Suriname, as a former colony of the Netherlands have a positive influence on trade relations between Indonesia and Suriname. In addition, the existence of the Embassy in Latin American countries and Latin American Embassy in Indonesia have a positive effect on the performance of RI-Latin America trade relations.